Case Study on the Use of an Unmanned Aerial System and Terrestrial Laser Scanner Combination Analysis Based on Slope Anchor Damage Factors - Chulhee Lee; Joonoh Kang (Remote Sensing)
This study utilized unmanned aerial systems (UAS) and terrestrial laser scanners (TLS) to develop a 3D numerical model of slope anchors and conduct a comprehensive analysis. Initial data were collected using a UAS with 4 K resolution, followed by a second dataset captured 6 months later with 8 K resolution after artificially damaging the anchor. The model analyzed damage factors such as cracks, destruction, movement, and settlement. Cracks smaller than 0.3 mm were detected with an error margin of ±0.05 mm. The maximum damaged area on the anchor head was within 3% of the designed value, and the volume of damaged regions was quantified. A combination analysis examined elevation differences on the anchor’s irregular bottom surface, resulting in an average difference at 20 points, reflecting ground adhesion. The rotation angle (<1°) and displacement of the anchor head were also measured. The study successfully extracted quantitative damage data, demonstrating the potential for an accurate assessment of anchor performance. The findings highlight the value of integrating UAS and TLS technologies for slope maintenance. By organizing these quantitative metrics into a database, this approach offers a robust alternative to traditional visual inspections, especially for inaccessible facilities, providing a foundation for enhanced safety evaluations.